Predictors of the Need for Permanent Pacemaker Implantation After Surgical Aortic Valve Replacement with a Biological Prosthesis and the Effect on Long-Term Survival - Ivo Deblier; Karl Dossche; Anthony Vanermen; Wilhelm Mistiaen (Journal of Cardiovascular Development and Disease)
The need for a permanent pacemaker (PPM) implantation after surgical aortic valve implantation (SAVR) is a recognized postoperative complication, with potentially long-term reduced survival. From 1987 to 2017, 2500 consecutive patients underwent SAVR with a biological valve with or without concomitant procedures such as CABG or mitral valve repair. Mechanical valves or valves in another position were excluded. Univariate and multivariate analyses were performed. The need for PPM implantation was documented in 2.7% of the cases. Patients with a postoperative PPM were older and had higher risk scores and a higher comorbid burden. Its predictors were a prior SAVR (odds ratio of 5.38, p < 0.001), use of a Perceval valve (3.94, p = 0.008), prior AV block 1–2 (2.86, p = 0.008), and pulmonary hypertension (2.09, p = 0.017). The need for PPM implantation was associated with an increased need for blood products, a prolonged stay in the ICU, and an increased 30-day mortality (2.5% vs. 7.0%, p = 0.005). The median survival decreased from 117 (114–120) to 90 (74–105) months (p < 0.001). The implantation had no significant effect on the freedom of congestive heart failure. The need for a PPM implant is not a benign event but might be a marker for a more severe underlying disease. Improving surgical techniques, especially with the Perceval rapid deployment valve, might decrease the need for a PPM implant.